ICA69 regulates activity-dependent synaptic strengthening and learning and memory - Chiu, Shu-Ling; Chen, Chih-Ming; Huganir, Richard L. (Frontiers in Molecular Neuroscience, 2023)
Long-term potentiation (LTP) is one of the major cellular mechanisms for learning and memory. Activity-dependent increases in surface AMPA receptors (AMPARs) are important for enhanced synaptic efficacy during LTP. Here, we report a novel function of a secretory trafficking protein, ICA69, in AMPAR trafficking, synaptic plasticity, and animal cognition. ICA69 is first identified as a diabetes-associated protein well characterized for its function in the biogenesis of secretory vesicles and trafficking of insulin from ER, Golgi to post-Golgi in pancreatic beta cells. In the brain, ICA69 is found in the AMPAR protein complex through its interaction with PICK1, which binds directly to GluA2 or GluA3 AMPAR subunits. Here, we showed that ICA69 regulates PICK1's distribution in neurons and stability in the mouse hippocampus, which in turn can impact AMPAR function in the brain. Biochemical analysis of postsynaptic density (PSD) proteins from hippocampi of mice lacking ICA69 (Ica1 knockout) and their wild-type littermates revealed comparable AMPAR protein levels. Electrophysiological recording and morphological analysis of CA1 pyramidal neurons from Ica1 knockout also showed normal AMPAR-mediated currents and dendrite architecture, indicating that ICA69 does not regulate synaptic AMPAR function and neuron morphology at the basal state. However, genetic deletion of ICA69 in mice selectively impairs NMDA receptor (NMDAR)-dependent LTP but not LTD at Schaffer collateral to CA1 synapses, which correlates with behavioral deficits in tests of spatial and associative learning and memory. Together, we identified a critical and selective role of ICA69 in LTP, linking ICA69-mediated synaptic strengthening to hippocampus-dependent learning and memory.